2017
DOI: 10.3354/meps12078
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of green turtles from Africa’s largest rookery assessed through genetic markers

Abstract: Marine turtles are highly migratory species that establish multiple connections among distant areas, through oceanic migration corridors. To improve the knowledge on the connectivity of Atlantic green turtles, we analysed the genetic composition and contribution to juvenile aggregations of one of the world's largest rookeries at Poilão Island, Guinea-Bissau. We amplified 856bp mitochondrial DNA (mtDNA) control region sequences of this population (n=171) containing the ~490bp haplotypes used in previous studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 66 publications
1
28
0
Order By: Relevance
“…All but one had been previously described in populations in the Caribbean Sea, South America, South Atlantic (Ascension Island; Formia, Godley, Dontaine, & Bruford, ) and Africa (Shamblin, Bagley et al, ; Shamblin, Dutton et al, ). The haplotypes found in our samples belonged to different lineages as defined in the literature (Naro‐Maciel et al, ): most haplotypes belonged to lineage A (84%), which is typically found in the Caribbean, while the rest belonged to lineage B (Figure ) typically found in South America, South Atlantic and Africa (Patrício et al, ; Shamblin, Bagley et al, ; Shamblin, Dutton et al, ). CM‐A5.1 is the only haplotype of lineage B found shared by both the captive and the wild populations; however, this haplotype is not exclusive of the South Atlantic region and can be found in other wild populations of the Caribbean region (Naro‐Maciel et al, ).…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…All but one had been previously described in populations in the Caribbean Sea, South America, South Atlantic (Ascension Island; Formia, Godley, Dontaine, & Bruford, ) and Africa (Shamblin, Bagley et al, ; Shamblin, Dutton et al, ). The haplotypes found in our samples belonged to different lineages as defined in the literature (Naro‐Maciel et al, ): most haplotypes belonged to lineage A (84%), which is typically found in the Caribbean, while the rest belonged to lineage B (Figure ) typically found in South America, South Atlantic and Africa (Patrício et al, ; Shamblin, Bagley et al, ; Shamblin, Dutton et al, ). CM‐A5.1 is the only haplotype of lineage B found shared by both the captive and the wild populations; however, this haplotype is not exclusive of the South Atlantic region and can be found in other wild populations of the Caribbean region (Naro‐Maciel et al, ).…”
Section: Resultssupporting
confidence: 52%
“…South Caribbean populations are AVE = Aves Island (Venezuela) and SUR = Matapica (Suriname) (Bolker, Okuyama, Bjorndal, & Bolten, ). South Atlantic populations are ASC = Ascension Island, BIO = Bioko Island (Equatorial Guinea), SAO = Sao Tome (Formia et al, ), TI = Trinidad Island (Trinidad y Tobago), RA = Rocas Atoll and FN = Fernando de Noronha (Brazil), and POI = Poilao (Guinea Bissau) (Patrício et al, ; Shamblin, Dutton et al, )…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Atlantic green turtle (Chelonia mydas) foraging grounds (n = 18, dark triangles and black star for study site) and nesting populations (n =14, gray circles) included in this study, with respect to major ocean currents: GfC: Gulf Current, NEC: North Equatorial Current, SEC: South Equatorial Current, BrC: Brazil Current, GC: Guinea Current, BgC: Benguela Current. Nesting populations: EcFL and SFL: Florida, USA (Shamblin et al, 2014); CUB: southwest Cuba (Ruiz-Urquiola et al, 2010); MEX: Quintana Roo, Mexico (Encalada et al, 1996); CR: Tortuguero, Costa Rica (Bjorndal et al, 2005b;Encalada et al, 1996); SUR: Matapica and Galibi, Suriname (Encalada et al, 1996;Shamblin et al, 2012); AV: Aves Island (Lahanas et al, 1998(Lahanas et al, , 1994Shamblin et al, 2012), Venezuela; BUC: Buck Island (Shamblin et al, 2012); RC/FN: Rocas Atoll and Fernando Noronha (Bjorndal et al, 2006;Encalada et al, 1996), Brazil; ASC: Ascension Island (Encalada et al, 1996;Formia et al, 2007); TRI: Trindade Island, Brazil (Bjorndal et al, 2006); GB: Poilão, Guinea-Bissau (Patrício et al, 2017); BIO: Bioko Island, Equatorial Guinea ; STP: Sao Tome and Principe . Foraging grounds: NC: North Carolina (Bass et al, 2006), HI: Hutchinson Island, Florida (Bass & Witzell, 2000), DT+EP: Dry Tortugas + Everglades Park, Florida (Naro-Maciel et al, 2016), SJ: St. Joseph Bay, Florida (Foley et al, 2007), TEX: Texas (Anderson et al, 2013), USA; BHM: Bahamas (Lahanas et al, 1998), CUL: Culebra, Puerto Rico (this study), BRB: Barbados (Luke et al, 2004), ALF: Almofala, Brazil (Naro-Maciel et al, 2007), RC: Rocas Atoll, Brazil ), FN: Fernando Noronha, Brazil (Naro-Maciel et al, 2012, BA: Bahia, Brazil , ES: Espirito Santo, Brazil , UB: Ubatuba, Brazil (Naro-Maciel et al, 2007), AI: Arvoredo Island, Brazil (Proietti et al, 2012), CB: Cassino Beach, Brazil (Proietti et al, 2012), BuA, Buenos Aires, Argentina (Prosdocimi et al, 2012), CV: Cape...…”
Section: Mixed Stock Analysis (Msa)mentioning
confidence: 99%